Pengaruh Advertising Content Value dan Influencer Credibility terhadap Attitude towards Brand dan Enrollment Intention; Studi Kasus Glints X Career Conference Indonesia - Brian Marco (Jurnal Strategi Pemasaran, 2021)
The Effect of Advertising Content Value and Influencer Credibility on Attitude towards Brand and Enrollment Intention; Case Study of Glints X Career Conference Indonesia. This study was made with the aim of analyzing the influence of Advertising Content Value and Influencer Credibility on Purchase Intention through Attitude towards Brand at Glints X Career Conference Indonesia. This research is conclusive and classified in the type of causal research using a quantitative approach. Data were collected through an online survey using a questionnaire instrument with responses that can be used from 100 respondents. Respondents are fresh graduates (graduated in 2020-2021) who have seen TikTok content about the Glints X Career Conference from influencer Vina Muliana (@vmuliana). The data is processed using a structural model equation approach with Partial Least Square Technique. The results of the study prove the influence of the Advertising Content Value and Influencer Credibility on Purchase Intention